Synthesis of 2-C-Substituted 5-Deoxyglucals from d-Ribose: Access to 2-C-Substituted 5-Deoxyglycosides and -Nucleosides - Polak, Peter; Cossy, Janine (Synlett, 2022)
The synthesis of 2-C-substituted 5-deoxyglucals from d-ribose, by using a nickel-catalyzed cross-coupling reaction of 2-iodo-5-deoxyglucals with Grignard reagents, is reported. The obtained 2-C-substituted 5-deoxyglucals were then transformed into 2-C-substituted 5-deoxyglycosides and 2-C-substituted 5-deoxynucleosides. During this work, structures published in the literature were reassigned.
Keywords: d-ribose; 5-deoxyglucal; 2-iodo-5-deoxyglucal; 2-C-substituted 5-deoxyglycoside; 2-C-substituted 5-deoxynucleoside; Grignard reagent; nickel catalysis.